The Effect of Product Quality and Product Packaging on Purchasing Decisions: Purchase Intention as a Mediating Variable - Umam, Aliqul Khoiril; Fikriah, Nur Laili (Journal of Economics Education and Entrepreneurship, 2024)
The purpose of this study was to analyze and test the effect of product quality and product packaging on purchasing decisions with purchase intention as a mediating variable on SilverQueen products for Gen Z in Malang City. This research is a quantitative study with a descriptive approach involving 135 Gen Z respondents from five districts in Malang City. The sample was taken using purposive sampling technique. The research location covers five sub-districts in Malang City, namely Blimbing, Kedungkandang, Klojen, Lowokwaru, and Sukun, with respondents who consume or have consumed SilverQueen products. Measurement of indicators on variables is carried out using a Likert Scale (1-5), which has five levels of answer preference. Data collection was done through an online questionnaire using Google Form, and the results were analyzed with Smart-PLS 4.0 statistical software. The research shows the following results: Product Quality has a negative influence on Purchasing Decisions on SilverQueen Chocolate Products as well as Product Packaging has no significant or negative effect on Purchasing Decisions for SilverQueen Chocolate Products. Product Quality has a positive influence on Purchase Intention on SilverQueen Chocolate Products. Product Packaging has no significant or negative effect on Buying Interest in SilverQueen Chocolate Products. Purchase Intention has a positive influence on Purchasing Decisions on SilverQueen Chocolate Products. The mediating relationship between Product Quality on Purchasing Decisions for SilverQueen Chocolate Products with Purchase Intention has a positive and significant effect. The mediating relationship between Product Packaging on Purchasing Decisions for SilverQueen Chocolate Products with Purchase Intention has a negative and insignificant effect.